2023
DOI: 10.1140/epjc/s10052-023-11298-0
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpreting deformed Heisenberg algebras

Abstract: Minimal and maximal uncertainties of position measurements are widely considered possible hallmarks of low-energy quantum as well as classical gravity. While General Relativity describes interactions in terms of spatial curvature, its quantum analogue may also extend to the realm of curved momentum space as suggested, e.g. in the context of Relative Locality in Deformed Special Relativity. Drawing on earlier work, we show in an entirely Born reciprocal, i.e. position and momentum space covariant, way that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Figure shows the direct current (DC) polarization curve of higher ionic conducting biopolymer membrane placed between two stainless steel blocking electrodes subjected to standard potential of 1.5 V at room temperature. [ 28 ] The polarization of current flow is detected as a function of time. As time increases the current gradually decreases and it gets constant after a long polarization period and the initial and final current are noted.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the direct current (DC) polarization curve of higher ionic conducting biopolymer membrane placed between two stainless steel blocking electrodes subjected to standard potential of 1.5 V at room temperature. [ 28 ] The polarization of current flow is detected as a function of time. As time increases the current gradually decreases and it gets constant after a long polarization period and the initial and final current are noted.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that modified Heisenberg algebras follow a similar pattern [16][17][18][19]: non-relativistic single-particle theories exhibiting a generalized uncertainty principle as well as a noncommutative geometry can be mapped onto theories yielding non-relativistic single-particle dynamics on curved momentum space. Here, the concept of curved momentum space refers to the theory of generalized Hamilton spaces (see [18,31] for more information).…”
Section: Curved Momentum Spacementioning
confidence: 98%
“…This ansatz may as well be applied in reversed order [18] such that a noncommutative space emerges from an underlying momentum space geometry. Along these lines, the kinematics of the non-relativistic single-particle quantum theory at hand are to be described in terms of the canonical positions Xi and momenta Pi , satisfying the algebra…”
Section: Curved Momentum Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Recent times have seen a merger of the areas of the GUP and curved momentum space, first through indication [90][91][92][93][94][95][96] and finally explicitly [97]. In particular, in [97][98][99] it was shown by direct construction that GUP-deformed theories can be mapped into quantum mechanics on nontrivial momentum space. Thus, in quantum theory a minimal length can be translated into a momentum-dependent metric.…”
Section: Introductionmentioning
confidence: 99%